1998
DOI: 10.4141/p97-067
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tillage management on yield performance in barley

Abstract: Therrien, M. C. and Grant, C. A. 1998. Effect of tillage management on yield performance in barley. Can. J. Plant Sci. 78: 301-303. A 3-yr study was conducted to assess the effect of tillage management on relative yield performance of selected cultivars of barley. The experiment was located on two differing textures of orthic black Chernozemic soils over 3 yr. Relative yields differed significantly between cultivars within tillage systems, and between tillage systems, sites and years. All interactions were als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 2 publications
1
6
0
Order By: Relevance
“…and CT following summer fallow in western Manitoba. Likewise, a cultivar × tillage interaction was detected for grain yield as well as for several quality parameters of six barley cultivars grown under comparable tillage systems to those reported by Therrien and Grant (1998) in a 5-yr study in northwestern North Dakota (Thompson and Hoag, 1987).…”
supporting
confidence: 56%
See 1 more Smart Citation
“…and CT following summer fallow in western Manitoba. Likewise, a cultivar × tillage interaction was detected for grain yield as well as for several quality parameters of six barley cultivars grown under comparable tillage systems to those reported by Therrien and Grant (1998) in a 5-yr study in northwestern North Dakota (Thompson and Hoag, 1987).…”
supporting
confidence: 56%
“…Ciha (1982) reported that a cultivar × tillage system interaction was not detected for grain yield and quality when four barley cultivars were grown under CT, NT, and a "conservation" or RT system in the Palouse region in southeastern Washington. Conversely, Therrien and Grant (1998) detected a cultivar × tillage interaction for grain yield of six barley cultivars grown under CT and NT following canola (Brassica spp.) and CT following summer fallow in western Manitoba.…”
mentioning
confidence: 96%
“…T he replacement of conventional or clean tillage (CT) with conservation tillage and particularly no‐tillage (NT) practices in the northern Great Plains is well documented (Therrien and Grant, 1998; Hansen et al, 2012). The enhanced precipitation‐use efficiency resulting from adoption of NT enabled farmers to intensify cropping systems, replacing traditional crop‐fallow with rotations where crops are grown annually (Anderson et al, 2003).…”
Section: Useful Conversionsmentioning
confidence: 99%
“…Yield is considered to be very low for cereals grown in developing countries compared with harvests in developed countries (Jaradat and Haddad 1994). Low barley yield is attributed to limited and uneven distribution of precipitation, poor soil moisture conservation, improper cultural practices, poor crop stands and weed competition (Therrien and Grant 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Low barley yield is attributed to limited and uneven distribution of precipitation, poor soil moisture conservation, improper cultural practices, poor crop stands and weed competition (Therrien and Grant 1998).…”
Section: Introductionmentioning
confidence: 99%